Performance evaluation of waste palm oil fiber reinforced stone matrix asphalt mixtures using traditional and sequential mixing processes - Yaro, N.S.A. (Elsevier Ltd, 2021)
Asphalt pavement in tropical countries like Malaysia faces severe distresses. Thus, the use of more resistant and stable asphalt mixtures on the surface layer like stone matrix asphalt concrete (SMAC) is encouraged. The performance-related properties of asphaltic concrete are highly influenced by the mixing process and the asphalt mixtures homogeneity and segregation are pivotal issues affecting asphaltic concrete production. Malaysian palm oil industry generates a large amount of waste palm fiber (WPOF) which are largely discarded. This study investigates the feasibility of utilizing WPOF as a stabilizer in SMAC and evaluates the influence of two different mixing processes (traditional and sequential) on its properties The SMAC mixtures were reinforced with various content of WPOF, 0â0.6 by weight of the total mix and evaluated for volumetric and mechanical properties. Several standard laboratory test methods were used to examine the mixtures: Marshall properties, drain down test, Cantabro, stiffness modulus, moisture damage test. The study revealed sequential mixing as a more viable mixing alternative for SMAC, as it shows lower drain down, air void, and optimum bitumen content with higher Marshall stability and voids in mineral aggregate values. While for the mechanical properties the sequential mixing shows higher moisture resistances, stiffness modulus, and less Cantabro loss for all mixture's types compared to the convention blends. It was observed that the optimum WPOF dosage is 0.3 for both mixing processes, Though, the sequential mixing shows improved mechanical properties. These improved properties are probably due to improving coating and proper dispersion of mixing materials during the mixing process. In conclusion, utilizing WPOF as stabilizers improve SMAC mixtures properties whereas, the sequential process produces better properties even at marginally lower OBC and mixing time. Â© 2021 The Authors